Lung microbiome: new insights into bronchiectasis’ outcome - Azoicai, Alice; Lupu, Ancuta; Alexoae, Monica Mihaela; Starcea, Iuliana Magdalena; Mocanu, Adriana; Lupu, Vasile Valeriu; Mitrofan, Elena Cristina; Nedelcu, Alin Horatiu; Tepordei, Razvan Tudor; Munteanu, Dragos; Mitrofan, Costica; Salaru, Delia Lidia; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
The present treatments for bronchiectasis, which is defined by pathological dilatation of the airways, are confined to symptom relief and minimizing exacerbations. The condition is becoming more common worldwide. Since the disease’s pathophysiology is not entirely well understood, developing novel treatments is critically important. The interplay of chronic infection, inflammation, and compromised mucociliary clearance, which results in structural alterations and the emergence of new infection, is most likely responsible for the progression of bronchiectasis. Other than treating bronchiectasis caused by cystic fibrosis, there are no approved treatments. Understanding the involvement of the microbiome in this disease is crucial, the microbiome is defined as the collective genetic material of all bacteria in an environment. In clinical practice, bacteria in the lungs have been studied using cultures; however, in recent years, researchers use next-generation sequencing methods, such as 16S rRNA sequencing. Although the microbiome in bronchiectasis has not been entirely investigated, what is known about it suggests that Haemophilus, Pseudomonas and Streptococcus dominate the lung bacterial ecosystems, they present significant intraindividual stability and interindividual heterogeneity. Pseudomonas and Haemophilus-dominated microbiomes have been linked to more severe diseases and frequent exacerbations, however additional research is required to fully comprehend the role of microbiome in the evolution of bronchiectasis. This review discusses recent findings on the lung microbiota and its association with bronchiectasis.